Meningkatkan Kemampuan Bahasa Ekspresif melalui Media Buku Pop-Up pada Anak Usia 3-4 Tahun - Lestari, Nurul Afiah; Nirmala, Ine; Syafrida, Rina (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Based on observations of language development in early childhood which is less than optimal in expressive language abilities. This research aims to investigate and determine the influence of pop up book media to improve expressive language skills in children aged 3-4 years at KB Mawar VII Karawang. The development of expressive language includes being able to convey what children feel, telling stories about simple experiences with simple sentences and answering questions. In this writing, the author uses the Classroom Action Research (PTK) method by carrying out two cycles with a target result of 71%. This research is shown on children's expressive language abilities. In the pre-action, children's expressive language abilities obtained an average percentage score of 28.5%. Furthermore, when the first cycle of action was carried out, the child's expressive language abilities increased to reach a percentage value of 46.6%. It is known that there has been an increase in cycle I but has not yet reached the target. Therefore, the researchers carried out cycle II actions and in this action the children's expressive language abilities increased with a percentage value of 85.5%. This states that this research is said to be successful because it can achieve the expected targets.